Clinical evaluation of autonomous, unsupervised planning integrated in MR-guided radiotherapy for prostate cancer. (March 2022) - Künzel, Luise A.; Nachbar, Marcel; Hagmüller, Markus; Gani, Cihan; Boeke, Simon; Wegener, Daniel; Paulsen, Frank; Zips, Daniel; Thorwarth, Daniela
Abstract: This retrospective study aimed at clinical evaluation of autonomous radiotherapy planning for ten prostate cancer cases, including organ-at-risk/target contouring and treatment planning. Five experts scored the clinical acceptability of each step using a 4-level Likert-scale resulting in 78%, 66% and 90% acceptance. For 6/10 patients the entire workflow was considered acceptable.